30 heritage buildings of Yangon inside the city that captured time - Rooney, Sarah 1970- (Serindia Publications, 2012)
"This volume is a compilation of 30 important colonial-era buildings in Yangon, Myanmar. It provides the history of each building and is illustrated with both present and old photographs"--Provided by publisher.